Prosthodontic Rehabilitation of a Patient with Velopharyngeal Insufficiency using Hollow Speech Aid Prosthesis - Basapogu, Sreeramulu; Ajay, P; Suman, P (Journal of Orofacial Research, 2015)
Rehabilitation of the missing oral and extraoral structures is one of the main aim of prosthodontics. Each patient has a different type of defect that presents with its own limitations and difficulties for successful rehabilitation. Defect of any extent resulting from surgical treatment of benign and malignant neoplasms, trauma or congenital defects causes problems in mastication, speech and esthetics. Pharyngeal obturator is a prosthesis which closes the palatal and pharyngeal defects and improving the speech and other functions. The following case report discusses about palatopharyngeal insufficiency, impression procedures, fabrication of prosthesis and improvements in speech.